Introducing microsoft infopath 2003 part 2 extending infopath solutions with BizTalk Server 2004. - Robbins, Thom
In Part I of this article (XML-J, Vol. 4, issue 6) we looked at creating a solution that used a new product in the Microsoft Office System 2003 called InfoPath. In this installment, I'll show you how to extend the solution created in Part I using BizTalk Server 2004.